Neolithic culinary traditions revealed by cereal, milk and meat lipids in pottery from Scottish crannogs - Hammann, Simon; Bishop, Rosie R.; Copper, Mike; Garrow, Duncan; Greenwood, Caitlin; Hewson, Lanah; Sheridan, Alison; Sturt, Fraser; Whelton, Helen L.; Cramp, Lucy J.E. (Nature Communications, 2022)
Cereal cultivation in Britain dates back to ca. 4000 BCE, probably introduced by migrant farmers from continental Europe. Widespread evidence for livestock appears in the archaeozoological record, also reflected by ubiquitous dairy lipids in pottery organic residues. However, despite archaeobotanical evidence for domesticated plants (such as cereals), organic residue evidence has been near-absent. Our approach, targeting low-abundance cereal-specific markers, has now revealed evidence for cereals (indicating wheat) in Neolithic pottery from Scottish 'crannogs', dating to ca. 3600 - 3300 BCE. Their association with dairy products suggests cereals may have been regularly prepared together as a milk-based gruel. We also observed a strong association between the occurrence of dairy products and smaller-mouthed vessels. Here, we demonstrate that cereal-specific markers can survive in cooking pots for millennia, revealing the consumption of specific cereals (wheat) that are virtually absent from the archaeobotanical record for this region and illuminating culinary traditions among early farming communities.
CRIS-Team Scopus Importer:2022-09-16